Las competencias profesionales del docente para la atención a los estudiantes con discapacidad intelectual moderada de educación general básica - Asencio Bohórquez, Nelly Shirley (2020)
The objective of this research work is to design a system of workshops that contribute to the development of professional competencies of teachers for the attention of students with moderate intellectual disabilities, Basic General Education, of the Carlos Matamoros Jara Educational Unit, of the Province Guayas The study is carried out through an investigation, which, according to the type of data used, is based on a mixed approach, since the application of quantitative and qualitative methods is combined: theoretical methods: analysis and synthesis, logical history, deductive inductive , hypothetical deductive, modeling, empirical methods: surveys, observations, documentary analysis and statistical methods: data were processed using SPSS20 software…………